2006
DOI: 10.1021/tx060084a
|View full text |Cite
|
Sign up to set email alerts
|

Replication of N2-Ethyldeoxyguanosine DNA Adducts in the Human Embryonic Kidney Cell Line 293

Abstract: N(2)-Ethyldeoxyguanosine (N(2)-ethyldGuo) is a DNA adduct formed by reaction of the exocyclic amine of dGuo with the ethanol metabolite acetaldehyde. Because ethanol is a human carcinogen, we assessed the biological consequences of replication of template N(2)-ethyldGuo, in comparison to the well-studied adduct O(6)-ethyldeoxyguanosine (O(6)-ethyldGuo). Single chemically synthesized N(2)-ethyldGuo or O(6)-ethyldGuo adducts were placed site specifically in the suppressor tRNA gene of the mutation reporting shut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…Studies in vitro indicate that the closely related adduct N 2 -ethyl-dGuo blocks trans-lesion DNA synthesis catalyzed by a variety of DNA polymerases potentially resulting in failure of replication or frameshift deletion mutations. Studies on mammalian cells showed that the lesion can be bypassed by other specific polymerases, suggesting that mammalian cells can accurately replicate past N 2 -ethyl-dGuo which is thus considered non-mutagenic (2729). However, this lesion could be mutagenic in particular contexts when polymerases are defective or reduced in their activity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in vitro indicate that the closely related adduct N 2 -ethyl-dGuo blocks trans-lesion DNA synthesis catalyzed by a variety of DNA polymerases potentially resulting in failure of replication or frameshift deletion mutations. Studies on mammalian cells showed that the lesion can be bypassed by other specific polymerases, suggesting that mammalian cells can accurately replicate past N 2 -ethyl-dGuo which is thus considered non-mutagenic (2729). However, this lesion could be mutagenic in particular contexts when polymerases are defective or reduced in their activity.…”
Section: Discussionmentioning
confidence: 99%
“…The blocking effect of N 2 -ethyl-Gua on DNA pols has been observed in both in vitro and cell-based assays [68]. In contrast to the blocking effects on replicative DNA pols the N 2 -ethyl-Gua adduct is bypassed by the Y-family DNA pols η, ι, and κ [6,912].…”
Section: Introductionmentioning
confidence: 99%
“…The N 2 -ethyl-Gua adduct is a strong block to DNA replication by replicative DNA polymerases in vitro and in cells (6,7). Structures of bacteriophage DNA polymerase (pol) RB69, a homolog of human DNA pol ␣, indicate a possible mechanism of N 2 -ethyl-Gua blocked DNA replication.…”
mentioning
confidence: 99%